ANALISIS KELAYAKAN FINANSIAL KEBUN KARET DI LAHAN GAMBUT DALAM RANGKA MENINGKATKAN PENDAPATAN PETANI TANAMAN SEMUSIM DI KECAMATAN SABANGAU KOTA PALANGKA RAYA - Sufri, Marwan; Sjarkowi, Fachrurrozie (Lampung University)
This socio-economic research was conducted in Kecamatan Sabangau, a subdistrict in the south-eastern part of Kota Palangka Raya, Central Kalimantan. The objectives of the study were: to calculate elasticity of net revenue against any change in value of each input cost of corn (Zea mays) and mustard green (Brasicca juncea) crops production as usually conducted by farmers, (2) to figure out financial feasibility indices of rubber (Hevea brasilensis) crop farming per hectare, on to which the seasonal crops are supposed to complement. Field observation was focused in 2 locations of the Sabangau subdistrict, namely Kelurahans Bereng Bengkel (20 respondents in total), and Kelurahan Kalampangan (40 respondents migrant farmers). The study shows that the seasonal crops could generate positive net revenue, yet insignificant. The elasticity index of net revenue of the production crop is insignificant. The crops farming are considerably risky against price fluctuation following limited market demand; Additional farming has to be created utilizing the existing arable land (about 1,5 hectares per farmer) suitable for rubber plantation. The NPV of the annual crop was Rp 26.461.838,00; IRR was 36,33 %; and B/C = 3,71 per hectare of rubber farming.